Composite diaphragm as well as preparation method and application thereof

By adding polymer fibers modified with hydrophilic groups to the porous layer of the composite separator to fix inorganic particles, the problems of insufficient mechanical strength and poor airtightness of the composite separator are solved, and higher mechanical strength and airtightness are achieved, ensuring the stability and safety of the electrolytic hydrogen production device.

CN119753753APending Publication Date: 2025-04-04XIAN LONGI HYDROGEN TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411997272.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing composite separators lack mechanical strength during the alkaline electrolytic hydrogen production process, making them difficult to withstand bending, and inorganic particles are prone to fall off, resulting in poor airtightness and affecting the stability and safety of the electrolytic hydrogen production device.

Method used

The porous layer is added with polymer fibers modified with hydrophilic groups. Through the hydrogen bond interaction between the polymer fibers and the inorganic particles, the inorganic particles are fixed in the organic polymer resin, thereby enhancing the mechanical strength and airtightness of the porous layer.

Benefits of technology

The mechanical strength and bending resistance of the composite diaphragm are improved, the fall of inorganic particles is reduced, the airtightness and stability of the diaphragm are enhanced, and the safety and sustainability of the electrolytic water hydrogen production device is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753753A_ABST
    Figure CN119753753A_ABST
Patent Text Reader

Abstract

The invention provides a composite diaphragm as well as a preparation method and application thereof, and belongs to the technical field of diaphragms. The composite diaphragm comprises a porous layer, the porous layer comprises organic polymer resin, inorganic particles and polymer fibers, and the polymer fibers are polymer fibers modified with hydrophilic groups.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of diaphragm technology, and specifically, to a composite diaphragm and a preparation method and application thereof. Background Art

[0002] The alkaline water electrolysis hydrogen production electrolyzer mainly includes water decomposition electrodes and diaphragms. In the process of water electrolysis, the electrolyzer produces oxygen on the anode electrode side and hydrogen on the cathode electrode side. The function of the diaphragm is to prevent hydrogen and oxygen from mixing with each other to ensure the purity of hydrogen. At the same time, the diaphragm must allow ions in the electrolyte to pass through to ensure the continuation of the electrolysis process. Summary of the invention

[0003] In view of this, in order to at least partially solve the above-mentioned technical problems, the present application provides a composite diaphragm and a preparation method and application thereof.

[0004] According to an embodiment of one aspect of the present application, a composite membrane is provided, comprising a porous layer; the porous layer comprises an organic polymer resin, inorganic particles and polymer fibers, wherein the polymer fibers are polymer fibers modified with hydrophilic groups.

[0005] According to an embodiment of another aspect of the present application, a method for preparing a composite membrane as described above is provided, comprising: mixing an organic polymer resin, inorganic particles, polymer fibers and a solvent to prepare a casting liquid; coating the casting liquid on a substrate or a porous support, performing a phase transformation, and obtaining a composite membrane.

[0006] According to another embodiment of the present application, there is provided an application of the composite diaphragm as described above in alkaline water electrolysis for hydrogen production, lithium batteries, zinc-air batteries, and liquid flow batteries.

[0007] According to the embodiments of the present application, by adding polymer fibers to the porous layer, mechanical support is provided for the porous layer, so that the diaphragm is resistant to bending, and the mechanical strength of the diaphragm can be improved. In addition, hydrogen bonds are formed between the hydrophilic groups modified by the polymer fibers and the inorganic particles. Combined with the strong interaction between the polymer fibers and the organic polymer resin, it helps to fix the inorganic particles in the organic polymer resin, effectively reducing the inorganic particles from falling off the porous layer, so that the diaphragm has better air tightness, which helps to maintain the stability and safety of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] The above and other objects, features and advantages of the present application will become more apparent through the following description of the embodiments of the present application with reference to the accompanying drawings, in which:

[0009] Figure 1 This is a flow chart of a method for preparing a composite diaphragm according to an embodiment of the present application. DETAILED DESCRIPTION

[0010] Below, embodiments of the present application will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present application. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present application. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present application.

[0011] The terms used herein are only for describing specific embodiments and are not intended to limit the present application. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0012] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).

[0013] In the process of producing hydrogen by electrolysis of water, hydrogen and oxygen are usually separated from the cathode and anode respectively with low energy consumption, and a diaphragm is set between the cathode and the anode to prevent the two gases from mixing and ensure the purity of hydrogen. At the same time, the function of ion transfer is retained, so that the electrolysis process forms a current loop, thereby ensuring the stability and sustainability of the electrolyzer. During the use of the electrolyzer, the diaphragm also needs to have good mechanical strength and be able to withstand the impact of the electrolyte and the generated gas for a long time.

[0014] The composite diaphragm in the related technology has poor mechanical strength and is not resistant to bending. In addition, during long-term use, inorganic particles easily fall off from the porous layer, which deteriorates the air tightness of the diaphragm, affecting the stability and safety of the water electrolysis hydrogen production device. It is difficult to simultaneously take into account the performance of ion permeability, mechanical strength and air tightness.

[0015] In the process of realizing the concept of this application, it was found that by adding polymer fibers into the porous layer, hydrogen bonding interactions were formed between the hydrophilic groups on the polymer fibers and the inorganic particles. Combined with the strong interaction between the polymer fibers and the organic polymer resin, it helps to fix the inorganic particles in the organic polymer resin.

[0016] Specifically, according to an embodiment of one aspect of the present application, a composite membrane is provided, comprising a porous layer having a plurality of micropores, the porous layer comprising an organic polymer resin, inorganic particles and polymer fibers, and the polymer fibers are polymer fibers modified with hydrophilic groups.

[0017] It should be noted that inorganic particles and organic polymer resins are important materials for forming the porous layer of the composite diaphragm. If inorganic particles or organic polymer resins are lost or fall off from the composite diaphragm, holes or cracks will appear in the composite diaphragm, thereby reducing the ability of the composite diaphragm to isolate gases. For example, in the process of hydrogen production by electrolysis of water, hydrogen or oxygen may pass through the diaphragm, causing the purity of hydrogen to decrease, which may seriously affect the safety of the hydrogen production device by electrolysis of water.

[0018] The present application fixes the inorganic particles on the porous layer by adding polymer fibers to the composite diaphragm, utilizing the hydrogen bonding interaction between the hydrophilic groups in the polymer fibers and the groups on the surface of the inorganic particles (such as hydroxyl groups, amino groups, etc.), and combining the strong interaction between the polymer fibers and the organic polymer resin. Relying on the high strength of the polymer fibers, a good support effect is provided, the bonding strength between the inorganic particles and the polymer fibers is strengthened, and the inorganic particles are further firmly targeted on the porous layer by the polymer fibers, so as to ensure that the diaphragm has good ion permeability and air tightness, and improve its stability and safety.

[0019] Furthermore, since the polymer fibers have relatively high strength, dispersing the polymer fibers in the porous layer can provide better support, so that the composite diaphragm is not prone to defects during use and has relatively high mechanical strength and aging resistance.

[0020] According to one or more embodiments of the present application, the hydrophilic group includes at least one of a sulfonic acid group, a carboxylic acid group, a phosphoric acid group (-PO(OH)3), a phosphonic acid group (-PO(OH)2), and a phosphinic acid group (-PO(OH)-). The above hydrophilic groups can not only form good hydrogen bond interactions with the groups in the inorganic particles, but also help to adsorb and transfer ions in the electrolyte, promote ion migration to form a current loop, and further improve the ion transmission performance of the composite diaphragm.

[0021] According to one or more embodiments of the present application, the fiber diameter of the polymer fiber is 10 to 5000 nm, for example, it can be 10 nm, 50 nm, 100 nm, 300 nm, 500 nm, 700 nm, 900 nm, 1000 nm, 1500 nm, 2000 nm, 3000 nm, 4000 nm or 5000 nm, preferably 100 to 1000 nm. If the diameter of the polymer fiber is too short, it is difficult to form a certain support effect; if the diameter is too wide, it is easy to precipitate during the preparation process and it is difficult to disperse in the solvent, so that the dispersion of the polymer fiber on the prepared porous layer is poor, which further affects the fixation of the inorganic particles, so that the air tightness and mechanical strength of the composite diaphragm are poor. The fiber length of the polymer fiber is 0.5 to 10 μm, for example, it can be 0.5 μm, 1 μm, 3 μm, 5 μm, 7 μm, 8 μm, 9 μm or 10 μm. If the fiber length is too long, it is easy to form a coiled structure like silk thread, which is easy to agglomerate and has poor dispersion, making it difficult to achieve uniform fixation of inorganic particles; if the length is too short, the support effect provided is relatively limited. Adjusting the diameter and length of the polymer fiber within a reasonable range helps to disperse the polymer fiber in the casting solution during the preparation process, so that its fiber structure provides uniform support and is not prone to defects, which helps to further enhance the mechanical strength of the composite diaphragm and further improve the bending resistance of the composite diaphragm.

[0022] Furthermore, the polymer fiber is selected from the group consisting of sulfonated polymer fiber, carboxylated polymer fiber, phosphorylated polymer fiber, phosphonated polymer fiber, and phosphinate polymer fiber.

[0023] According to one or more embodiments of the present application, the organic polymer resin is a cast polymer. In the present application, it is understood that the cast polymer is a polymer used to form a matrix in the process of forming a composite diaphragm. The organic polymer resin as a matrix is ​​conducive to the uniform dispersion of polymer fibers and inorganic particles, and helps to improve the bonding strength between the polymer fibers and the inorganic particles.

[0024] According to one or more embodiments of the present application, the molar percentage of the hydrophilic group in the polymer fiber is less than or equal to 50%. Based on the fact that the polymer fiber has good strength, alkali resistance, resistance to impact of high and low temperature changes, and good insulation performance, the molar percentage of the hydrophilic group is adjusted within the above range, which can avoid dissolution in the solvent during the preparation process, and is not easy to swell in the solvent, so that the polymer fiber expands, thereby ensuring that the polymer fiber has a uniform supporting effect on the porous layer.

[0025] Further, when the hydrophilic group is a sulfonic acid group, the molar percentage of the sulfonic acid group in the polymer fiber is less than or equal to 10%, for example, it can be 5%, 6%, 7%, 8%, 9% or 10%; when the hydrophilic group is a carboxylic acid group, a phosphoric acid group, a phosphonic acid group, or a phosphinic acid group, the molar percentage of the carboxylic acid group, the phosphoric acid group, the phosphonic acid group or the phosphinic acid group in the polymer fiber is less than or equal to 50%, preferably less than 30%. Based on different hydrophilic groups, when the molar percentage range is respectively limited to the above range, it helps to stably disperse the polymer fiber in the solvent and provide uniform support. When it is prepared into a composite membrane, it can enhance the mechanical strength of the composite membrane, make the composite membrane resistant to bending, and further reduce the possibility of inorganic particles falling off from the porous layer.

[0026] The molar percentage of the hydrophilic group in the polymer fiber can be determined by titration, elemental analyzer, nuclear magnetic resonance spectroscopy or infrared absorption spectroscopy, or other methods known in the art.

[0027] The polymer fiber modified with the hydrophilic group can be prepared by introducing the hydrophilic group into the polymer fiber without the hydrophilic group, or by polymerizing the monomer containing the hydrophilic group and spinning the obtained polymer with the hydrophilic group into fiber. The introduction can be carried out by methods known in the art, for example, the sulfonic acid group can be introduced into the polymer fiber by sulfonation, for example, using sulfonation reagents such as concentrated sulfuric acid and oleum. For example, the phosphoric acid group is introduced into the polymer fiber by nucleophilic phosphination reaction, for example, the phosphoric acid group is introduced into the polymer fiber by reacting diethyl phosphite with a halogenated polymer. For example, a polymer containing carboxylic acid is prepared by copolymerizing an unsaturated carboxylic acid monomer (such as acrylic acid, etc.) with an olefin monomer containing a carbon-carbon double bond (such as styrene, etc.), and then spinning into a polymer fiber containing carboxylic acid.

[0028] According to an embodiment of the present application, the polymer fiber includes at least one of polyphenylene sulfide, polyetheretherketone, polypropylene, and polytetrafluoroethylene. The polymer fiber has good strength, high alkali resistance, high and low temperature resistance, and good insulation.

[0029] According to one or more embodiments of the present application, the mass percentage of polymer fibers in the porous layer is 0.01-10%, for example, it can be 0.01%, 0.1%, 1%, 2%, 3%, 4%, 4.5%, 5%, 6%, 8% or 10%, preferably 0.1-6%. If the polymer fibers are excessive in the porous layer, although the mechanical strength is improved, the ionic conductivity will be reduced, which is not conducive to the formation of a current loop. Especially when the polymer fibers exceed 10%, the reduction in ionic conductivity is large. If the polymer fibers are too few, such as less than 0.01%, the support for the porous layer is limited due to the small amount added, and it is difficult to provide uniform support, and the anti-bending effect on the composite diaphragm is not obvious.

[0030] According to one or more embodiments of the present application, the composite membrane further comprises a porous support; the porous layer covers the surface of the porous support and fills the through holes of the porous support. By adding the porous support to the composite membrane, the porous layer and the porous support work together to further improve the support and mechanical strength of the composite membrane.

[0031] The porous support is polyethylene, polypropylene, polysulfone, polyethersulfone, polyphenylsulfone, polyphenylene sulfone, polyketone, polyimide, polyetherimide, fluorine-based resin, or the like.

[0032] The fluorine-based resin is ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polychlorotrifluoroethylene, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer, etc. Preferably, it is at least one of polypropylene and polyphenylene sulfide.

[0033] The porous support may contain only one of the listed polyethylene, polypropylene, polysulfone, polyethersulfone, polyphenylene sulfone, polyphenylene sulfide, polyketone, polyimide, polyetherimide, fluorine resin, etc., or may contain two or more thereof. From the aspect of excellent heat resistance and alkali resistance, at least one of polypropylene and polyphenylene sulfide is preferred, and more preferably selected from polyphenylene sulfide.

[0034] According to one or more embodiments of the present application, the porous support has no limitation on its form, and may be at least one of a non-woven fabric, a woven fabric, a knitted mesh, and a porous membrane, for example, a mixed fabric of a non-woven fabric and a woven fabric, preferably a knitted mesh. The porous support preferably comprises a knitted mesh of polyphenylene sulfide.

[0035] When the porous support is in the form of a woven mesh, the mesh number of the porous support is 40 to 200 meshes, for example, 40 meshes, 50 meshes, 80 meshes, 100 meshes, 150 meshes or 200 meshes, preferably 50 meshes, to provide a more uniform and stable support effect.

[0036] The thickness of the porous support body when it is in sheet form is not limited, for example, it is 30~2000μm, and can be 30μm, 100μm, 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm, 900μm, 1000μm, 1100μm, 1200μm, 1300μm, 1400μm, 1500μm, 1600μm, 1700μm, 1800μm, 1900μm or 2000μm, preferably 50~1000μm, more preferably 80~500μm, and further preferably 80~300μm.

[0037] The thickness of the porous support can be determined by observing a cross section using a field emission scanning electron microscope (FE-SEM). For example, the average value of thicknesses at any five points can be used as the thickness of the porous support.

[0038] According to one or more embodiments of the present application, the inorganic particles may include metal hydroxides, metal oxides, metal nitrides, metal inorganic salts, and the like.

[0039] The inorganic particles may include one of the metal hydroxides, metal oxides, metal nitrides, and metal inorganic salts listed above, or may include two or more of them.

[0040] The metal elements in the metal hydroxide, metal oxide and metal nitride are selected from magnesium, zirconium, titanium, zinc, aluminum, tantalum, hafnium and cerium; preferably, the inorganic particles are selected from metal hydroxides or metal oxides of magnesium, zirconium, titanium, zinc, aluminum and tantalum; sulfates of calcium, barium, lead and strontium; nitrides of titanium, zirconium and hafnium.

[0041] The metal inorganic salt is selected from calcium sulfate, barium sulfate, lead sulfate, strontium sulfate, barium titanate, potassium titanate, preferably barium sulfate. From the aspect of improving the ion conductivity of the composite diaphragm, metal hydroxides or metal oxides are preferred, magnesium hydroxide, zirconium hydroxide, titanium hydroxide, zirconium oxide, titanium oxide, magnesium oxide, cerium oxide is more preferred, and zirconium oxide is particularly preferred.

[0042] The inorganic particles can be surface treated, for example, using a known surface treatment agent such as a silane coupling agent, stearic acid, oleic acid, or a phosphate ester. The shape of the inorganic particles is not limited, and can be amorphous, granular, granular, flaky, hexagonal plate-like, or fibrous. From the perspective of improving the interaction with the polymer fiber, preferably granular, flaky, or plate-like, more preferably flaky or plate-like. From the perspective of improving the strength of the composite diaphragm, preferably flaky or plate-like, more preferably flaky.

[0043] The average particle size of the inorganic particles is not limited. From the perspective of improving the strength of the composite separator, it is preferably 0.01 to 2.0 μm, for example, 0.01 μm, 0.05 μm, 0.08 μm, 0.1 μm, 0.5 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm or 2 μm. It is more preferably 0.08 μm to 1.5 μm, and further preferably 0.1 μm to 1 μm.

[0044] The average particle size refers to the volume average particle size (D50) obtained by particle size distribution measurement by laser diffraction. Specifically, the particle size distribution is measured using a laser diffraction / scattering particle size distribution measuring device, and the median particle size (D50) in the volume-based particle size distribution is taken as the average particle size. It should be noted that the particles are mixed in ethanol, ultrasonic irradiation is performed to disperse them, and the resultant is used as a measurement sample.

[0045] From the perspective of providing a composite separator having excellent alkali resistance and durability and good strength, the inorganic particles are preferably zirconium oxide. The average particle size of zirconium oxide is preferably 0.01 to 2.0 μm as described above.

[0046] According to one or more embodiments of the present application, the organic polymer resin includes polyethylene terephthalate, polybutylene terephthalate, polynaphthalate, butanediol, polystyrene, polysulfone, polyethersulfone, polyphenylene sulfide, polyphenylene sulfide, polyarylate, polyetherimide, polyimide, polyamide-imide, polyphenylene ether, polyarylether nitrile, etc. The organic polymer resin can be one of the above materials, or it can contain two or more. From the aspect of excellent heat resistance and alkali resistance, it is preferably selected from at least one of polysulfone, polyethersulfone, polyaryletherketone, polyphenylene ether, and polyarylether nitrile; from the aspect of being easily soluble in solvents, polysulfone is more preferably selected.

[0047] The average molecular weight of the organic polymer resin is greater than 35000, for example, it can be 35000, 40000, etc., which will not be described in detail here. When the average molecular weight of the organic polymer resin exceeds 35000, it has good mechanical strength.

[0048] From the viewpoints of heat resistance, alkali resistance and easy solubility in solvents, the organic polymer resin is preferably polysulfone. The average molecular weight of polysulfone is greater than 35,000 as mentioned above.

[0049] According to one or more embodiments of the present application, the porous layer may further include a hydrophilic additive, which may be an organic hydrophilic additive or an inorganic hydrophilic additive. The organic hydrophilic additive is a water-soluble polymer such as polyvinyl pyrrolidone, polyethylene glycol, polyethylene oxide, polyvinyl alcohol, polyethyleneimine with a molecular weight of less than 100,000, polyacrylic acid, etc.; the inorganic hydrophilic additive is a water-soluble salt, preferably a metal chloride such as calcium chloride, magnesium chloride, lithium chloride, sodium chloride, potassium chloride, etc. The addition of the above hydrophilic additive helps to improve the hydrophilicity of the composite diaphragm, thereby improving the ion conduction effect of the composite diaphragm and helping to form a current loop.

[0050] The mass content of the hydrophilic additive in the composite diaphragm is preferably 0.001-20% relative to 100% by mass of the inorganic particles, for example, 0.001%, 0.005%, 0.01%, 0.1%, 1%, 5%, 10%, 15% or 20%, and more preferably 0.01-10%.

[0051] According to one or more embodiments of the present application, the thickness of the composite membrane is 10 to 1000 μm, for example, 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm or 1000 μm, preferably 400 to 500 μm. The porosity is 40 to 80%, for example, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, preferably 55 to 65%. Maintaining the thickness and porosity of the composite membrane in the above ranges, respectively, helps to maintain good mechanical strength, good air tightness, and high ion conduction effect.

[0052] According to one or more embodiments of the present application, the mass ratio of the organic polymer resin, the inorganic particles, and the polymer fibers is preferably (10-30): (20-50): (0.01-10), for example, 10:20:0.01, 15:25:0.1, 12.1:40.7:4.5, 12:45:2, 15:40:3, 20:50:5, 25:50:4, 30:50:10, etc. Adjusting the mass ratio of the three to the above range helps to better fix the inorganic particles in the organic polymer resin through the polymer fibers, effectively prevent the inorganic particles from falling off from the porous layer, and improve the stability of the composite separator.

[0053] It should be noted that the composite diaphragm may contain other additives as required.

[0054] According to another embodiment of the present application, a method for preparing the composite diaphragm as described above is provided. Figure 1 Flow chart of the method for preparing the composite diaphragm of the present application embodiment, as shown in Figure 1 As shown, the method includes operations S101-S102.

[0055] In operation S101, an organic polymer resin, inorganic particles, polymer fibers, and a solvent are mixed to prepare a casting solution.

[0056] Operation S101 is a process for preparing a casting solution by mixing several raw materials with a solvent. The mixing method and procedure are not limited. The mixing method can be a known method, and for example, a mixer, a ball mill, a jet mill, a disperser, a sand mill, a roller mill, a pot mill, etc. can be used. The mixing procedure can be arbitrary. For example, the three components of organic polymer resin, inorganic particles and polymer fibers can be mixed in a solvent simultaneously or in an arbitrary order. In addition, the organic polymer resin, inorganic particles and polymer fibers can be mixed in a solvent separately, and their mixed solutions can be mixed.

[0057] From the viewpoint of easily dissolving the organic polymer resin and better dispersing the three raw materials, the solvent may be at least one of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, and N,N-dimethylformamide.

[0058] In operation S102, the casting solution is coated on a substrate or a porous support, and phase conversion is performed to obtain a composite membrane.

[0059] Operation S102 is a step of coating the casting solution obtained in operation S101 on a substrate or a porous support to form a composite membrane. The method of coating the casting solution on the substrate may be die coating, spin coating, gravure coating, spraying, or a method using a coater.

[0060] The substrate is a film or sheet made of a resin such as polybutylene terephthalate, polyethylene naphthalate, polypropylene, polyethylene, polyvinyl chloride, polyvinyl acetal, polymethyl methacrylate, polycarbonate, or the like, or a glass plate.

[0061] The method of coating the casting solution on the porous support is direct coating or dip coating, for example, a coating machine can be used. Direct coating can be understood as a method of directly coating the casting solution on the porous support, and dip coating can be understood as a method of immersing the porous support in the casting solution.

[0062] The coating film can be arranged on one side of the porous support or on both sides. The coating film can be entirely laminated on the surface of the porous support, or a portion can be impregnated in the porous support and the remaining portion can be laminated on the surface of the porous support. In the manner in which the coating film is impregnated in the porous support, the coating film can be impregnated in a certain depth in the thickness direction of the porous support, or in the entire thickness direction of the porous support. By appropriately adjusting the coating method, the viscosity of the casting solution, etc., the degree of the coating film impregnation in the porous support can be adjusted. By regulating the coating process, the thickness of the coating film can be controlled.

[0063] Phase inversion is a method of preparing a coating into a porous layer, for example, a non-solvent-induced phase inversion method can be used. When a liquid containing a non-solvent is brought into contact with the coating, the non-solvent diffuses into the coating. At this time, the solvent in the coating that is soluble in the non-solvent is dissolved from the coating, so that the organic polymer resin that is insoluble in the non-solvent solidifies to form a porous layer.

[0064] When the coating film does not contain polymer fibers, the interaction between the organic polymer resin and the inorganic particles in the coating film is not particularly strong. In the present application, polymer fibers are added to the casting solution to firmly fix the inorganic particles in the organic polymer resin by using the polymer fibers.

[0065] The method of bringing the coating film into contact with the liquid containing the non-solvent is a method of immersing the coating film in the liquid containing the non-solvent (coagulation bath).

[0066] It should be noted that the non-solvent can be understood as a property that the organic polymer resin is substantially insoluble. The coating film is brought into contact with the non-solvent and immersed in a liquid containing the non-solvent. Substantially insoluble organic polymer resin refers to a situation where the solubility of the polymer resin relative to 100g of solvent at 25°C is less than 100mg. The non-solvent can be water such as pure water, distilled water, ion-exchanged water; lower alcohols such as methanol, ethanol, propanol; or mixed solvents thereof. From the perspective of being conducive to post-processing, water is preferred, and ion-exchanged water is more preferred.

[0067] There is no limit to the temperature of the liquid containing the non-solvent when it contacts the coating. From the perspective of facilitating uniform solidification of the coating, it can be 10-50°C. There is no limit to the time for which the coating is immersed in the liquid containing the non-solvent. The porosity, pore structure and pore size of the porous layer can be controlled by controlling the process conditions of the coagulation bath.

[0068] Optionally, the coating film may be pre-evaporated before the coagulation bath as required. It is understood that the prepared coating film is exposed to the vapor containing the non-solvent of the organic polymer resin.

[0069] The temperature of the non-solvent-containing gas when in contact with the coating film is not limited. The time for which the coating film is in contact with the non-solvent-containing gas is preferably 10 to 80 seconds.

[0070] Through the above operations S101-S102, a porous layer containing organic polymer resin, inorganic particles and polymer fibers is obtained, and the porous layer can be used as a composite diaphragm. From the above process, it can be seen that the porous layer may contain non-solvent or solvent components in the coating. The porous layer can be further dried as needed.

[0071] In addition to the above operations, a known process such as a pressing process may be performed as necessary to make the density of the composite separator more uniform.

[0072] The composite separator has a porous layer containing an organic polymer resin, inorganic particles and polymer fibers, and preferably further comprises a porous support.

[0073] In one specific embodiment, without adding a porous support, the preparation process of the composite membrane is as follows:

[0074] Dissolve polysulfone in a certain amount of N-methylpyrrolidone (NMP), use mechanical stirring to fully dissolve for 12 hours, add a certain amount of zirconium oxide, continue to disperse for 24 hours using a high-speed disperser, continue to add a certain amount of sulfonated polyphenylene sulfide fiber, ultrasonically disperse for 24 hours, apply with a doctor blade, pre-evaporate, and immerse in a coagulation bath to form a porous membrane.

[0075] In one specific embodiment, when a porous support is added, the preparation process of the composite membrane is as follows:

[0076] Dissolve polysulfone in a certain amount of N-methylpyrrolidone, use mechanical stirring to fully dissolve for 12 hours, add a certain amount of zirconium oxide, continue to disperse with a high-speed disperser for 24 hours, continue to add a certain amount of sulfonated polyphenylene sulfide fiber, ultrasonically disperse for 24 hours, use a coater to coat it on a 50-mesh polyphenylene sulfide (PPS) support net, pre-evaporate and then immerse it in a coagulation bath to form a porous membrane.

[0077] According to another embodiment of the present application, there is provided an application of the composite diaphragm as described above in alkaline water electrolysis for hydrogen production, lithium batteries, zinc-air batteries, and liquid flow batteries.

[0078] It can be understood that the composite diaphragm prepared in the present application has good ion conductivity and gas barrier properties, as well as high mechanical strength. When used in alkaline water electrolysis to produce hydrogen, it has alkali resistance and high and low temperature resistance. In addition, due to the addition of polymer fibers, it has good mechanical strength, which effectively reduces the shedding of inorganic particles and improves the safety and stability in alkaline water electrolysis to produce hydrogen.

[0079] When used in lithium batteries, the composite separator helps prevent short circuits because the modification of hydrophilic groups helps reduce the interfacial resistance of the composite separator, increase the migration speed of lithium ions, and improve the overall performance of the battery.

[0080] When applied to zinc-air batteries, the modification of hydrophilic groups makes the composite membrane helpful in introducing catalytic active sites, which can promote the oxygen reduction reaction. At the same time, the porosity of the composite membrane can be appropriately adjusted to optimize the oxygen transmission path.

[0081] When applied to liquid flow batteries, it helps to improve the selective passage of target ions. Since the working environment of liquid flow batteries is relatively harsh, the composite diaphragm of the present application has good stability and corrosion resistance, can be used for a long time, and improves the reliability and service life of liquid flow batteries.

[0082] The present application is further described below by embodiments, drawings and related test experiments and results thereof. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the present application embodiments. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined arbitrarily into other feasible embodiments.

[0083] It should be noted that the following specific examples are only for illustration, and the protection scope of this application is not limited thereto. The chemicals and raw materials used in the following examples are all commercially available or homemade by recognized processing methods.

[0084] It should be noted that the tests of tensile strength, surface resistance and bubble point of the composite diaphragm all use national standard test methods. Surface resistance can be understood as the resistance value per unit width and unit length, and bubble point can be understood as the pressure value at which the liquid is squeezed out of the maximum pore size of the material by the gas to form the first continuous bubble. The tensile strength test refers to the test method described in "GB / T1040.3 Determination of Plastic Tensile Properties Part 3 Film / Thin Film Test Conditions", and the surface resistance test method refers to the area resistance test method described in "SJ / T10171 General Test Method for Basic Properties of Alkaline Battery Diaphragms". The bubble point test method refers to the test method described in "GB / T32361 Separation Membrane Pore Size Test Method Bubble Point and Average Flow Method". The porosity is tested using the mercury intrusion method, and the amount of mercury adsorbed by the material is measured by the mercury intrusion instrument to calculate the porosity and pore size distribution of the material. The stability test uses an accelerated aging test. During the test, a diaphragm with a weight of W1 is placed in a hydrothermal reactor containing 30wt% KOH at 120°C and heated for 50 hours. The diaphragm is then taken out, washed three times with deionized water, dried, and weighed. The weight is recorded as W2. The weight retention rate of the diaphragm after accelerated aging can be obtained by calculate.

[0085] Embodiment 1:

[0086] The mass percentages of the raw materials in Example 1 are 12.1% polysulfone, 4.5% sulfonated polyphenylene sulfide fiber, 40.7% zirconium oxide (average particle size 100 nm), and 42.7% NMP, wherein the sulfonic acid group content in the sulfonated polyphenylene sulfide fiber is 8%, the fiber diameter is 100 nm, and the length is 8 μm.

[0087] Preparation process: dissolve polysulfone in NMP, use mechanical stirring to fully dissolve for 12 hours, add zirconium oxide, continue to disperse for 24 hours with a high-speed disperser, continue to add sulfonated polyphenylene sulfide fiber, ultrasonically disperse for 24 hours, apply with a doctor blade, pre-evaporate, immerse in a coagulation bath, and form a porous membrane 1.

[0088] Embodiment 2:

[0089] The formula of raw materials in this embodiment 2 is the same as that in embodiment 1.

[0090] Preparation process: Dissolve polysulfone in a certain amount of N-methylpyrrolidone, use mechanical stirring to fully dissolve for 12 hours, add zirconium oxide, continue to disperse it with a high-speed disperser for 24 hours, continue to add sulfonated polyphenylene sulfide fiber (SPPS), ultrasonically disperse it for 24 hours, use a coater to coat it on a 50-mesh polyphenylene sulfide (PPS) support net, pre-evaporate it, and then immerse it in a coagulation bath to form a porous membrane 2.

[0091] Comparative Example 1:

[0092] The preparation process of Comparative Example 1 is substantially the same as that of Example 1, except that no sulfonated polyphenylene sulfide fiber is added in Comparative Example 1 to form the porous membrane 1'.

[0093] Comparative Example 2:

[0094] The preparation process of Comparative Example 2 is substantially the same as that of Example 2, except that sulfonated polyphenylene sulfide fibers are not added in Comparative Example 2 to form the porous membrane 2'.

[0095] The examples 1 and 2 of the present application and the comparative examples 1 and 2 were tested respectively, and the relevant test results are shown in Table 1 below.

[0096] Comparative Example 3:

[0097] The preparation process of Comparative Example 1 is substantially the same as that of Example 1, except that in Comparative Example 1, the sulfonated polyphenylene sulfide fiber is replaced with polyphenylene sulfide fiber, the fiber having a diameter of 100 nm and a length of 8 μm, to form a porous membrane 3 ′.

[0098] Table 1 Properties of porous membranes prepared in Examples and Comparative Examples

[0099]

[0100] As shown in Table 1, it can be seen from the comparison between Example 1 and Comparative Example 1 that after adding sulfonated polyphenylene sulfide fiber, the prepared porous membrane has higher tensile strength, higher bubble point pressure, and higher surface resistance. After the accelerated aging test, the stability of the porous membrane of Example 1 is relatively better. It can be seen from the comparison between Example 2 and Comparative Example 2 that after further adding the PPS support net, the performance of the two porous membranes is effectively improved, but the various indicators of Example 2 are improved more, and are better than the relevant performance of Comparative Example 2. It can be seen from the comparison between the results of Example 1 and Example 2 that after further adding the porous support net on the basis of Example 1, the tensile strength is highly improved, and the bubble point pressure and surface resistance are improved to varying degrees, and the effect of accelerated aging can still be maintained. Therefore, it can be judged that adding the porous support net is a better choice.

[0101] By comparing Example 1 and Comparative Example 3, it can be seen that the use of sulfonated polyphenylene sulfide fibers can rely on the interaction between the sulfonic acid group and zirconium oxide, and combined with the strong interaction between the sulfonated polyphenylene sulfide fibers and polysulfone, the fixation of zirconium oxide can be synergistically achieved, so that Example 1 has better tensile strength, bubble point pressure and surface resistance than Comparative Example 3. At the same time, Example 1 has more superior anti-aging properties and can be widely promoted in composite diaphragms.

[0102] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present application. It should be understood that the above description is only a specific embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A composite membrane comprising a porous layer, The porous layer includes an organic polymer resin, inorganic particles and polymer fibers, and the polymer fibers are polymer fibers modified with hydrophilic groups.

2. The composite diaphragm according to claim 1, wherein: The hydrophilic group includes at least one of a sulfonic acid group, a carboxylic acid group, a phosphoric acid group, a phosphonic acid group, and a phosphinic acid group.

3. The composite diaphragm according to claim 1, wherein: The fiber diameter of the polymer fiber is 10-5000 nm, preferably 100-1000 nm; The fiber length of the polymer fiber is 0.5-10 μm.

4. The composite diaphragm according to claim 1, wherein: The organic polymer resin is a film casting polymer.

5. The composite diaphragm according to claim 1, wherein: The polymer fibers are selected from sulfonated polymer fibers, carboxylated polymer fibers, phosphorylated polymer fibers, phosphonated polymer fibers, and phosphinate polymer fibers.

6. The composite diaphragm according to any one of claims 1 to 5, wherein The molar percentage of the hydrophilic groups in the polymer fiber is less than or equal to 50%.

7. The composite diaphragm according to claim 6, wherein: The hydrophilic group is a sulfonic acid group, and the molar percentage of the sulfonic acid group in the polymer fiber is less than or equal to 10%; or The hydrophilic group is a carboxylic acid group, a phosphoric acid group, a phosphonic acid group, or a phosphinic acid group, and the molar percentage of the carboxylic acid group, the phosphoric acid group, the phosphonic acid group, or the phosphinic acid group in the polymer fiber is less than or equal to 50%, preferably less than 30%.

8. The composite diaphragm according to any one of claims 1 to 5, wherein The mass percentage of the polymer fiber in the porous layer is 0.01-10%, preferably 0.1-6%.

9. The composite diaphragm according to any one of claims 1 to 5, wherein The polymer fiber includes at least one of polyphenylene sulfide, polyetheretherketone, polypropylene and polytetrafluoroethylene.

10. The composite diaphragm according to claim 1, wherein: The composite diaphragm also includes a porous support; The porous layer covers the surface of the porous support and fills the through holes of the porous support.

11. The composite diaphragm according to claim 10, wherein: The porous support includes at least one of polyethylene, polypropylene, polysulfone, polyethersulfone, polyphenylsulfone, polyphenylene sulfide, polyketone, polyimide, polyetherimide, and fluorine-based resin, preferably at least one of polypropylene and polyphenylene sulfide.

12. The composite diaphragm according to claim 10 or 11, wherein: The porous support body comprises at least one of a non-woven fabric, a woven fabric, a woven mesh, and a porous membrane; The thickness of the porous support is 30 to 2000 μm, preferably 50 to 1000 μm, more preferably 80 to 500 μm, and further preferably 80 to 250 μm.

13. The composite diaphragm according to claim 12, wherein: The porous support is in the form of a woven mesh, and the mesh number of the porous support is 40 to 200 meshes.

14. The composite diaphragm according to any one of claims 1 to 5, wherein The inorganic particles include at least one of metal hydroxides, metal oxides, metal nitrides, and metal inorganic salts.

15. The composite diaphragm according to any one of claims 14, wherein: The average particle size of the inorganic particles is 0.01 to 2 μm, preferably 0.08 to 1.5 μm, and more preferably 0.1 to 1 μm.

16. The composite diaphragm according to claim 14, wherein: The metal element in the metal hydroxide, metal oxide, or metal nitride is selected from magnesium, zirconium, titanium, zinc, aluminum, tantalum, hafnium, or cerium; The metal inorganic salt is selected from calcium sulfate, barium sulfate, lead sulfate, strontium sulfate, barium titanate, and potassium titanate; Preferably, the inorganic particles are selected from metal hydroxides or metal oxides of magnesium, zirconium, titanium, zinc, aluminum, and tantalum; sulfates of calcium, barium, lead, and strontium; and nitrides of titanium, zirconium, and hafnium.

17. The composite diaphragm according to claim 14, wherein: The inorganic particles are selected from magnesium hydroxide, zirconium hydroxide, titanium hydroxide, zirconium oxide, titanium oxide, cerium oxide, barium sulfate, and magnesium oxide.

18. The composite diaphragm according to any one of claims 1 to 5, wherein The organic polymer resin includes at least one of polyethylene terephthalate, polybutylene terephthalate, polynaphthalate, butanediol, polystyrene, polysulfone, polyethersulfone, polyphenylene sulfide, polyphenylene sulfide, polyarylate, polyetherimide, polyimide, polyamideimide, polyphenylene ether, and polyarylether nitrile, preferably at least one of polysulfone, polyethersulfone, polyaryletherketone, polyphenylene ether, and polyarylether nitrile; The average molecular weight of the organic polymer resin is greater than 35,000.

19. The composite diaphragm according to any one of claims 1 to 5, wherein: The porous layer further comprises a hydrophilic additive, and based on the mass of the inorganic particles, the mass proportion of the hydrophilic additive is 0.001-20%, preferably 0.01-10%; The hydrophilic additive includes an organic hydrophilic additive or an inorganic hydrophilic additive. The organic hydrophilic additive is a water-soluble polymer, and the inorganic hydrophilic additive is a water-soluble salt.

20. The composite diaphragm according to any one of claims 1 to 5, wherein The composite membrane has a thickness of 10-1000 μm, preferably 400-500 μm; and a porosity of 40-80%, preferably 55-65%.

21. The composite diaphragm according to any one of claims 1 to 5, wherein The mass ratio of the organic polymer resin, the inorganic particles and the polymer fibers is (10-30): (20-50): (0.01-10).

22. A method for preparing a composite diaphragm according to any one of claims 1 to 21, comprising: Mixing organic polymer resin, inorganic particles, polymer fibers and solvent to prepare a casting solution; The casting solution is coated on a substrate or a porous support, and phase conversion is performed to obtain the composite diaphragm.

23. Use of the composite diaphragm as claimed in any one of claims 1 to 21 in alkaline water electrolysis for hydrogen production, lithium batteries, zinc-air batteries and flow batteries.

Citation Information

Patent Citations

  • Composite diaphragm as well as preparation method and application thereof

    CN118621367A

Cited By

  • Composite diaphragm, preparation method of composite diaphragm, alkaline electrolytic cell and application of alkaline electrolytic cell

    CN121204735A

  • Composite separator, preparation method therefor, and use thereof

    WO2026144520A1